Influences of Marketing Mix Elements on Ecotourism Clientele - Jimma Zone, Southwest Ethiopia - Shimekit Kelkay Eshete; Derara Ketma Teressa; Wubshet Kassa Wubie; Sukarn Sharma (Journal of Indonesian Tourism and Development Studies, 2020)
This study assessed the influence of marketing mix elements (7 Ps i.e. Product, Price, Place, Promotion, People, Process, and Physical Evidence) on ecotourism clientele in Jimma Zone, South West Ethiopia. According to the data received from the Jimma Zone Cultural and Tourism office, a total of 23 woredas are under the Jimma zone. From these, the researchers selected six, which are endowed with ecotourism resources. The target population for this study was all Government staff working here and the research was conducted in July 2019. The study adopted a census or total enumeration method because the total population of the study was small. The instrument for the study consists of a structured questionnaire. Multiple regression analysis and descriptive statistics were used as a method for data analysis. The findings of the study revealed that physical evidence made the highest contribution followed by product development, promotion, process, people and place on ecotourism clientele. It implies marketing mix elements enhance ecotourism development, and the key stakeholders should consider the proper implementation of such marketing mix elements for sustainable development and promotion of ecotourism in the Jimma zone.